The Use of Direct Marketing Techniques in Sport Marketing - Gardan, Daniel; Epuran, Gheorghe; Gardan, Iuliana Petronela (Annals of Spiru Haret University. Economic Series, 2016)
Adapting marketing principles and concepts to sport related services and products domain represents a challenge for any specialist in the field because the specific features that are characteristic for the needs, motivations and consumption process itself. In order to achieve different quantitative and qualitative marketing communication objectives, sports involved organizations are developing a communication mix adapted to the channels used by the consumers. Among the communication tools used are found also the direct marketing techniques that have had a tremendous development during the last 25 years and so. The article will analyze the process of building a efficient direct marketing communication with sport consumers and the implications of using such instruments and tools for the future activity of sport related organizations. Some future research lines are proposed and conclusions are stated on the matter.